Tax Management, Tax Regulations, and Tax Literacy on Corporate Taxpayer Compliance: Mediation of Tax Restitution - Kusbiantora, Mahmud; Asmara, Rina Yuliastuty (International Journal of Economics Development Research (IJEDR), 2025)
This study examines corporate tax obligations influenced by tax management, tax regulations, and tax literacy, with tax restitution as a mediating variable supported by Tax Compliance Theory and Behavioral Tax Theory. This study uses a quantitative research approach that specifically adopts a causal research design (explanatory), which explains how the diversity of independent and mediating variables affects corporate taxpayer compliance at the Jakarta Tebet Pratama Tax Office so that it can provide a strong framework for empirical analysis. Data were obtained through a questionnaire scale of 1 - 5. The population in this study refers to all corporate taxpayers registered at the Jakarta Tebet Pratama Tax Office (Kantor Pelayanan Pajak/KPP), totaling 14,845 taxpayers. Sampling was carried out using proportional random sampling so that a sample of at least 374 corporate taxpayers could be obtained as a unit of analysis. Data analysis used descriptive and inferential analysis using Partial Least Squares Structural Equation Modeling (PLS-SEM). The empirical research results prove that tax management, tax regulations, and tax literacy, with tax restitution as a mediator, can positively and significantly influence corporate tax obligations. These results provide substantive implications that in order to improve taxpayer compliance, attention needs to be given not only to improving tax literacy, tax system management, and clarity of tax rules but also to taxpayer experience in the tax restitution process. A transparent, fast, and fair restitution process can strengthen the relationship between these factors and tax compliance. In this case, a comprehensive and taxpayer-oriented tax policy can potentially increase state revenues by increasing taxpayer compliance (individuals and corporations).